2010
DOI: 10.1111/j.1600-6143.2010.03231.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Incidence of Colorectal Malignancies in Renal Transplant Recipients: A Case Control Study

Abstract: This study was to evaluate the frequency of colorectal neoplasia in renal transplant recipients and to investigate the association with Epstein-Barr virus (EBV) and cytomegalovirus (CMV) infection. We compared the frequency of colorectal neoplasia among renal transplant recipients with that of the healthy subjects. Specimens of colorectal neoplasia were examined for EBV and CMV using in situ hybridization and immunohistochemistry, respectively. Of 796 renal transplantation cohorts, 315 were enrolled. The frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 30 publications
1
37
0
2
Order By: Relevance
“…In our study, we compared KTR and CP with the same type of CRC. In agreement with previous reports (11,12), we found that kidney function was higher and there was a trend for mean age different at time of neoplasia and long-term immunosuppression for CRC in KTR. Our results did not reach significance probably because of the sample size, as Spier et al reported (11).…”
Section: Discussionsupporting
confidence: 95%
See 3 more Smart Citations
“…In our study, we compared KTR and CP with the same type of CRC. In agreement with previous reports (11,12), we found that kidney function was higher and there was a trend for mean age different at time of neoplasia and long-term immunosuppression for CRC in KTR. Our results did not reach significance probably because of the sample size, as Spier et al reported (11).…”
Section: Discussionsupporting
confidence: 95%
“…Although we found fewer adenomas than other lesions in KTR (16.7%), the percentage was equivalent to that of another group with a higher prevalence (20%) (12). Adenoma is the premalignant lesion with the greatest impact on outcome in patients with CRC.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Several studies have reported a two-to three-fold increased risk for colorectal cancer in transplant recipients compared to the general population [170][171][172][173][174][175][176][177] . In transplant recipients, colorectal cancer may present at an earlier age and may be more aggressive 175,178 .…”
Section: Other Non-infectious Causesmentioning
confidence: 99%